Restless Leg Syndrome in Patients with Multiple Sclerosis and its Effect on Frequency of Daytime Sleepiness and Fatigue of the Patients - Ashjazadeh, Nahid; Shamszadeh, Zahra (Galen Medical Journal, 2016)
Background: Restless leg syndrome (RLS), fatigue and daytime sleepiness are three known co-morbidities in patients with multiple sclerosis (MS). The aim of this study was to evaluate the frequency of RLS in patients with MS and its effect on the frequency of fatigue and daytime sleepiness in these patients. Material and Methods: One hundred twenty patients who referred to the Inpatients Neurology Ward of Chamran hospital, affiliated with the Shiraz University of Medical Sciences, from June 2014 to March 2015, were selected as the study participants. The patients with clinically definite MS, according to the 2010 Revised Mc-Donald criteria, and expanded disability status scale (EDSS) â‰¤5.5 were included. RLS, fatigue and daytime sleepiness were assessed by the criteria of the International RLS study group (IRLSSG), fatigue severity scale (FSS) and Epworth sleepiness scale (ESS) respectively and the related statistical analyzes were conducted. Results: Seventy eight patients (65%) met all the four IRLSSG criteria, 77 patients (64.1%) suffered from fatigue and only 36 patients (30%) had excessive daytime sleepiness. RLS was not significantly linked to mean age, sex, MS duration, and daytime sleepiness of the studied MS patients, but fatigue was more frequent in MS patients with RLS, which was statistically significant (P=0.018). Conclusion: The main result of this study is that RLS is a common comorbidity in MS and the patients with MS, who also suffer from RLS. They have frequently experienced higher fatigue symptoms than those without RLS. Therefore, the appropriate diagnosis and management of RLS may improve both RLS and fatigue in these patients. [GMJ. 2016;5(1):7-12]